2003
DOI: 10.1046/j.1523-536x.2003.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Satisfaction with Their Involvement in Health Care Decisions During a High‐Risk Pregnancy

Abstract: Although most women want to be actively involved in health decision-making during a high-risk pregnancy, some prefer a passive role. The setting of prenatal care, community-based or in-hospital, was less important than the ability of nurses and physicians to support the woman in her preferred role in decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 20 publications
3
65
2
2
Order By: Relevance
“…In contrast, consistent with hypothesis (H2), it was found that provision of information, constructive communication, and good relationships, all predicted elevated satisfaction with health services. These findings extend previous research demonstrating the importance of providing patients with information regarding their care in a warm and reassuring fashion (Di Blasi et al, 2001;Harrison et al, 2003). Moreover, in partial support of our third hypothesis (H3), patient distress interacted with one of the three patient-provider relationships, namely, the information aspect.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, consistent with hypothesis (H2), it was found that provision of information, constructive communication, and good relationships, all predicted elevated satisfaction with health services. These findings extend previous research demonstrating the importance of providing patients with information regarding their care in a warm and reassuring fashion (Di Blasi et al, 2001;Harrison et al, 2003). Moreover, in partial support of our third hypothesis (H3), patient distress interacted with one of the three patient-provider relationships, namely, the information aspect.…”
Section: Discussionsupporting
confidence: 88%
“…A qualitative study of women with high risk pregnancies showed 30 of the 47 participants wished to be involved in decision making. Following the birth of their children, five of the remaining 17 women said that in future pregnancies they would also want to take a more active role in their care (Harrison et al 2003). Shared decision making in pregnancy is also associated with more positive emotions on the part of women (VandeVusse 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many antenatal interventions have been shown to reduce neonatal morbidity and mortality [4]; however, evidence for the effectiveness of antenatal care in reducing maternal mortality (and to a lesser extent, morbidity) is less compelling [5].…”
Section: Discussionmentioning
confidence: 99%